Pulverização eletrostática nas culturas de soja e milho: efeitos na deposição de calda e eficácia biológica - Assunção, Heli Heros Teodoro de (2019)
The electrostatic spray can bring benefits to the application of phytosanitary products, among them the reduction in the rate of application and the increase of deposits on the targets. However, little information exists on your employment in soybean crops (Glycine max (L.) Merrill) and maize (Zea mays (L.)). The objective this work was to evaluate the efficiency to the electrostatic spray, in conjunction with the use of lower rates of application and different adjuvants in the spray deposition on plants of soybean and corn plants and in chemical control of powdery mildew of soybean (Microsphaera diffusa Cooke & Peck). Experiments were carried out in the field for both crops. The experimental design was a randomized block design with 4 replications, in a 2 x 2 x 2 + 1 factorial scheme, with 2 application rates (95 and 52 L ha-1), with and without droplet electrification, 2 compositions of syrup (mineral oil and synthetic adjuvant) with the addition of adjuvante of low and high electrical conductivity ) and 1 additional treatment (control without application). Were evaluated the droplet spectrum, the deposition of the syrup, the loss to the soil and, for soybean, the effectiveness of the control of powdery mildew. To analyze the spray deposition on plants and the soil added to a marker to the syrups. It was then extracted for quantification, by means of spectrophotometry, the deposition in upper and lower leaves of the canopy and in petri plates placed on the ground. In the soybean was sprayed a fungicide syrup (azoxystrobin + benzovindiflupir) and the corn an insecticidal syrup (fenpropatrin). Were also evaluated the physicochemical properties of the silts (electrical conductivity, density, viscosity and surface tension) and the load / mass ratio induced in drops by electrostatic equipment. All treatments, regardless of application technique, showed control of the causative pathogen of powdery mildew of soybean. The electrostatic spray presented benefits for the application in some situations and responded positively to the increase of electrical conductivity of syrup. In the soybean crop, did not influence the loss to the soil, which was higher with the increase of the rate of application. In corn, the deposition of the pulverized syrup increased in the upper third and decreased the loss to the soil.